Violence and the sacred - Girard, Rene; Gregory, Patrick (New York : Bloomsbury Academic, 2013)
"Violence and the Sacred is René Girard's landmark study of human evil. Here Girard explores violence as it is represented and occurs throughout history, literature and myth. Girard's forceful and thought-provoking analyses of Biblical narrative, Greek tragedy and the lynchings and pogroms propagated by contemporary states illustrate his central argument that violence belongs to everyone and is at the heart of the sacred."--
Keywords: Rites and ceremonies; Sacrifice